2017
DOI: 10.1007/s12288-017-0903-z
|View full text |Cite
|
Sign up to set email alerts
|

Reasons for Discarding of Whole Blood/Red Cell Units in a Regional Blood Transfusion Centre in Western India

Abstract: To analyze the reason for discarding whole blood and red cell concentrates in a Regional Blood Transfusion Centre in India. Retrospective analysis of electronic data on collection of blood and reason for discard of whole blood and red cell concentrate between January 2012 and December 2016. 1,70,431 units of blood were collected between January 2012 and December 2016 in various blood donation camps. On an average 6.60% whole blood or red cell units were discarded because of various reasons. Out dating was the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 14 publications
1
9
0
1
Order By: Relevance
“…Blood product wastage is an important consideration for blood collectors and hospitals, and it is an especially acute issue in LMIC where replacement products might not be readily available. This is one of the few surveys of blood product wastage that specifically targeted these countries [5,6]. As a whole, the results of this study tend to confirm that wastage of RBCs is variable and could reach high percentages in these countries making supply difficult to manage.…”
Section: Discussionsupporting
confidence: 56%
See 2 more Smart Citations
“…Blood product wastage is an important consideration for blood collectors and hospitals, and it is an especially acute issue in LMIC where replacement products might not be readily available. This is one of the few surveys of blood product wastage that specifically targeted these countries [5,6]. As a whole, the results of this study tend to confirm that wastage of RBCs is variable and could reach high percentages in these countries making supply difficult to manage.…”
Section: Discussionsupporting
confidence: 56%
“…<5% b. 5 Eighteen respondents reported that being able to split RBC components, using systems that maintain sterility, would be useful. When asked how many split volume RBCs it would be useful to obtain from a full volume RBC, 10 suggested 2 split RBC components, 6 said 3, 5 said 4, 2 said 6 and 1 suggested 10.…”
Section: All Quesɵons Are Based On the Calendar Year (1 Stmentioning
confidence: 99%
See 1 more Smart Citation
“…This kind of wastage may be reduced by better management of blood bag collection, storage and utilization. 11,12 Polcythemia accounted for 20% of blood discard in our study. These patients came to blood bank for the purpose of therapeutic phlebotomy and the blood units collected from them were subjected to discard as the same cannot be utilized for blood replacement.…”
Section: Discussionmentioning
confidence: 51%
“…As for the financial costs of potentially avoidable whole blood and blood component disposals, it has been estimated at approximately R$ 760 million, equivalent to approximately US$ 2 million, if we consider that only one unit of packed red blood cells costs, with underestimated values, R$ 150 or US$ 39.9. An Indian study found that in a large blood bank, the disposal of 6,777 units of whole blood and red blood cells (2012-2016) by expiration alone accounted for approximately US$ 100,000, considering a unit value of US$ 15 (19) .…”
Section: Discussionmentioning
confidence: 99%